2020
DOI: 10.1007/s40314-020-1082-3
|View full text |Cite
|
Sign up to set email alerts
|

Fractional-order mathematical model for calcium distribution in nerve cells

Abstract: Calcium (Ca 2+) ions are known as a second messenger, involved in a variety of signalling process. It regulates various physiological processes like signal transduction, proliferation, etc. Calbindin-D 28k reacts with free Ca 2+ ions and significantly lowers down the cytosolic free calcium concentration ([Ca 2+ ]) in nerve cell. Voltage-gated calcium channel (VGCC) works as an outward source of Ca 2+ which initiates and sustains Ca 2+ signalling process for the smooth functioning of the cells. An alteration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…13,14 The fractional calculus is not limited to any particular branch but is used in chemistry, biochemistry, biology, engineering, physics, hydrology, and medicine. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] Yavuz and Bonyah, 29 in their paper, examined the fractional-order schistosomiasis model via exponential law kernel and Mittag-Leffler kernel in Liouville-Caputo sense. The iterative scheme through Laplace transform and Sumudu-Picard integration technique was applied for the solution of their model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 The fractional calculus is not limited to any particular branch but is used in chemistry, biochemistry, biology, engineering, physics, hydrology, and medicine. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] Yavuz and Bonyah, 29 in their paper, examined the fractional-order schistosomiasis model via exponential law kernel and Mittag-Leffler kernel in Liouville-Caputo sense. The iterative scheme through Laplace transform and Sumudu-Picard integration technique was applied for the solution of their model.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, it finds a great application in real‐life modeling problems, especially biological systems 13,14 . The fractional calculus is not limited to any particular branch but is used in chemistry, biochemistry, biology, engineering, physics, hydrology, and medicine 15–28 . Yavuz and Bonyah, 29 in their paper, examined the fractional‐order schistosomiasis model via exponential law kernel and Mittag–Leffler kernel in Liouville–Caputo sense.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there have been several experimental attempts that were performed in the past to identify the role and physiological impact of sodium calcium exchangers on various cells [13,14,15,16]. Beside this a researches has explored the role of parameters of calcium toolkits on astrocytes [17,18,19,20,21,22], neuron [23,24,25,26,27,28,29,30], oocytes [31,32], myocytes [33,34,35], hepatocytes [36], and T lymphocytes cells [37,38]. Thus a very little amount of work has attempted to study parameters of calcium toolkits by using the fractional calculus approach.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, complex systems can be modeled using multiple temporal and spatial scales without segmenting the given problem into a lot of smaller ones. Recently, numerous fractional calculus applications in neuroscience field have been explored [10][11][12][13][14][15][16]. The researchers [10][11][12] showed that the membrane ion channels, conductances, spiny dendrites and the spiking activities of neurons have the feature of fractional calculus.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous fractional calculus applications in neuroscience field have been explored [10][11][12][13][14][15][16]. The researchers [10][11][12] showed that the membrane ion channels, conductances, spiny dendrites and the spiking activities of neurons have the feature of fractional calculus. Lundstrom et al [13] showed that the neocortical pyramidal neurons have fractional order adaptation that depends on the changes of fractional order stimulus.…”
Section: Introductionmentioning
confidence: 99%